How Universities Entrust Digital Literacy to Improve Student Learning Outcomes During the COVID-19 Disruption - Abd. Basir; Kamaliah Kamaliah; Arman Harahap; Ahmad Fauzi; Budi Karyanto (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
Since the policy of sending students home to study as a result of responding to the dangers of the pandemic, universities around the world have increasingly trusted distance learning solutions. The solution was to rely on digital literacy to continue and improve student learning outcomes during the COVID-19 disruption. For this reason, the researchers have proven it through analytical efforts and in-depth studies in several international publications. In short, the researchers examined each piece of evidence with a phenomenological approach to get answers to research questions that are among other things, involve a data coding system, critical evaluation, and drawing of valid and reliable final results. The data discussion concludes that world universities believe that digital technology that was increasingly trending can become a learning innovation even though the world will continue to hit global education. Hence, the researchers hope that these findings should support other studies in the future. Keywords: Digital Literacy, Learning Outcomes, Entrust Digital Literacy